Anadara kagoshimensis (Mollusca: Bivalvia: Arcidae) in Adriatic Sea: morphological analysis, molecular taxonomy, spatial distribution, and prediction - STRAFELLA, PIERLUIGI; FERRARI, ALICE; FABI, GIANNA; SALVALAGGIO, VERA; PUNZO, ELISA; CUICCHI, CLARA; SANTELLI, ANGELA; CARIANI, ALESSIA; TINTI, FAUSTO; TASSETTI, ANNA NORA; SCARCELLA, GIUSEPPE (Mediterranean Marine Science, 2018)
Morphological analysis, molecular characterization, and information on distribution and density of Anadara kagoshimensis (Tokunaga, 1906) specimens collected in the Adriatic Sea were here carried out as based on various material and data from five surveys conducted from 2010 to 2014, for a total of 329 bottom trawl hauls. The morphological and molecular analyses allowed to clarify the confused taxonomy regarding the biggest ark clam alien species invading the Italian waters and the Mediterranean Sea. The analysis on distribution and density revealed that A. kagoshimensis mostly occurs along the Italian coast at depths from 8 to 50 m, with a catch frequency of more than 98% in all hauls performed on silty-clay sediment at 8-30 m depth. The hotspot map clearly shows a reduction of its distribution area from 2010 to 2012.